Os biocombustíveis no plano nacional de energia e a garantia do direito fundamental ao ambiente equilibrado - Pereira, Leonardo Martins (2018)
The present dissertation’s goal is to verify if there are public policies that concretize the right to a clean environment in Brazilian legal framework. By defining biofuel as a National Agency of Petroleum competence, the country changed biofuel into a commodity, despising its assets, that is to say: environmental protection, social necessity and life quality. Thus, the problem faced when analyzing Brazilian’s energy sector is the possibility of biofuel usage as an alternative to petroleum. Here, we take into account the scenario presented on the National Energy Plan 2030 (NEP 2030), with a critical and transparent vision, aiming to indicate a way to the trilemma Energy Planning, Biofuel and Fundamental Rights to a Safe Environment. This research provides data to eventual changes in national public policies that can lead to a more rational use of energy sources. The present work is justified by the need to discuss the theme in order to protect the next generations; since either by negligence or ignorance a limited and highly pollutant energy matrix was established as a state policy. This research topic appeared due to an interest born in the graduate program in biofuel, when looking for periodical reviews of energy matrixes applied to all Brazilian regions, taking into account the conventional and alternative sources, as well as the technologies available as a result of anachronistic public policies. This research results also point to the necessity to concretize the fundamental principle of a safe and equilibrated environment. As a conclusion, the Brazilian energy matrix do not guarantee the effective usage of biofuel due to a lack of planning, proper handling, investments and adequate public policies. This dissertation uses the deductive method, with a bibliographic and documental research, having the legal dogma as a formal objective, without losing sight of the social, political and economic objectives. The adopted methodology pursuit the scientific knowledge, cognoscere, analyzing documents, laws, legislative annals, legal doctrines, legal opinions, as well as governmental plans and strategies. In this way, we find solutions, acquire knowledge and provide information that can be used in a practical way for biotechnological, industrial and agricultural production.